Ответ:
Объяснение:
H2CO3 = H(+) + HCO3(-) ( H(+) -катион водорода, HCO3(-)- гидрокарбонат анион)
HCO3(-) = H(+) + CO3(2-) (Н(+) - катион водорода, СО3(2-) - карбонат анион)
H2CO3 = 2H(+) + CO3(2-)
диссоциация процесс обратимый
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
H2CO3 = H(+) + HCO3(-) ( H(+) -катион водорода, HCO3(-)- гидрокарбонат анион)
HCO3(-) = H(+) + CO3(2-) (Н(+) - катион водорода, СО3(2-) - карбонат анион)
H2CO3 = 2H(+) + CO3(2-)
диссоциация процесс обратимый